2017
DOI: 10.1016/j.nbd.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Preventive motor training but not progenitor grafting ameliorates cerebellar ataxia and deregulated autophagy in tambaleante mice

Abstract: Authors' contributionEF and KL performed grafts; EF performed motor training, behavioral, immunohistochemical analyses and stereological counts; MG and EB performed molecular biology and biochemical experiments; EF, FR, KL and AB conceived experiments, EF, KL and AB interpreted data and wrote the manuscript; all the authors reviewed and approved the final manuscript. Highlights• Preventive grafts of Purkinje cells survive despite ongoing host neurodegeneration correlates. Our results demonstrate that, despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…We initially observed clear motor abnormalities in a number of adult mutant mice, suggesting possible cerebellar defects. To precisely address functional cerebellar abnormalities in Sox2 mutants, we subjected them to behavioral tests of motor coordination and equilibrium, used to detect alterations that arise following cerebellar damage: the rotarod and balance beam tests (Fuca et al, ; Hilber & Caston, ). We compared motor performances of mutants and control littermates between 1 and 8 months of life (Figure b–d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We initially observed clear motor abnormalities in a number of adult mutant mice, suggesting possible cerebellar defects. To precisely address functional cerebellar abnormalities in Sox2 mutants, we subjected them to behavioral tests of motor coordination and equilibrium, used to detect alterations that arise following cerebellar damage: the rotarod and balance beam tests (Fuca et al, ; Hilber & Caston, ). We compared motor performances of mutants and control littermates between 1 and 8 months of life (Figure b–d).…”
Section: Resultsmentioning
confidence: 99%
“…Motor coordination, balance, and motor learning were assessed using an accelerating rotarod (Ugo Basile, Varese, Italy; Fuca et al, ). The rotarod apparatus had five flanges dividing the five 5.7‐cm lanes, the cylinder diameter was 3.5 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Consistently, pharmacological treatments targeting autophagy provided beneficial effects in several models of hereditary cerebellar ataxia [168][169][170][171]. Moreover, positive outcomes associated with changes in autophagy were also induced by motor training administered at presymptomatic stages in the tambaleante (tbl) mouse model of ataxia [172]. In tbl mice [173], alteration of the HERC1 E3 ubiquitin ligase leads to overactive autophagic processes resulting in massive degeneration of Purkinje neurons [163].…”
Section: Cellular Mechanisms Underlying Functional Cerebellar Reservementioning
confidence: 89%
“…In tbl mice [173], alteration of the HERC1 E3 ubiquitin ligase leads to overactive autophagic processes resulting in massive degeneration of Purkinje neurons [163]. Motor exercise favored tbl Purkinje neuron survival, reduced atrophy, increased afferent contacts to mutant Purkinje neurons, and allowed partial circuit stabilization, with moderate positive motor consequences [172]. This was accompanied by autophagy attenuation and increased BDNF, a key signal underlying both neuroprotection and neural plasticity [174].…”
Section: Cellular Mechanisms Underlying Functional Cerebellar Reservementioning
confidence: 99%
“…Studies in rats and mice showed that motor training prevents or reduces cerebellar degeneration caused by alcoholicinduced degeneration disease, age, and also SCA 1 (mouse model) (Carro et al 2001;Larsen et al 2000;Fryer et al 2011). Fuca et al (2017) found that motor training led to increased survival of Purkinje cells and cerebellar circuitry in tambaleante mutant mice. Exercising demanding and new complex multi-joint movements appear to outperform "pure exercise" (Klintsova et al 2004;Kleim et al 2007;Black et al 1990).…”
Section: Animal Cerebellar Lesion Models Indicate Long-term Adaptatiomentioning
confidence: 99%